George Boyd Smith journal - Smith, George Boyd, 1839-1893.
Photocopy, together with annotated typescript, of Smith's journal entries written before his enlistment and while serving in the Confederate army with the 61st Tennessee Infantry and mentioning the siege of Vicksburg, the Shenandoah Valley campaign (1862), and the battle of Antietam.
In part, photocopy.
Confederate soldier of Sullivan County, Tenn.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Confederate States of America. -- Army. -- Tennessee Infantry Regiment, 61st.; Antietam, Battle of, Md., 1862.; Shenandoah Valley Campaign, 1862.; Vicksburg (Miss.) -- History -- Siege, 1863.; Sullivan County (Tenn.) -- History; Tennessee -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Campaigns; United States -- History -- Civil War, 1861-1865 -- Personal narratives, Confederate; Soldiers -- Confederate States of America